Kinerja Aparatur Pemerintah Desa Dalam Peningkatan Kualitas Pelayanan Publik Di Desa Tapenpah, Kecamatan Insana, Kabupaten Timor Tengah Utara - Bekun, Stefanus; Fina, Yohanes (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2024)
Public service is the most realistic and intensive transaction arena between the people and the government, active interaction between service providers and recipients is an important part of the process of building public participation and accountability. Public service providers must demonstrate the quality of service provided to the public, through the performance provided. The work performance shown by the village government with service motivation is to provide the best service to the community, the ability of the apparatus in fairly good service and service opportunities make it easier for village officials and the community to access types of administrative services in the village. The performance shown by the Tapenpah village government can improve the quality of public services in the village.